(untitled) (Biomolecules and Biomedicine, 2020)
Telomeres are repetitive DNA sequences located at the end of chromosomes that serve as a protective barrier against chromosomal deterioration during cell division. Approximately 50–200 base pairs of nucleotides are lost per cell division, and new repetitive nucleotides are added by the enzyme telomerase, allowing telomere maintenance. Telomere shortening has been proposed as an indicator for biological aging, but its relationship with age-related osteoporosis is ambiguous. We summarize the current evidence on the relationship between telomere length and bone health in experimental and epidemiological studies, which serve as a scientific reference for the development of novel diagnostic markers of osteoporosis or novel therapeutics targeting telomere and telomerase of bone cells to treat osteoporosis.